Strengthening Inclusive Education by Examining Factors Affecting Universal Design for Learning (UDL) Implementation in Elementary School: A Systematic Literature Review - Dea Karlina; Farida Kurniawati; Wahyuni Christyani Martono (AL-ISHLAH: Jurnal Pendidikan, 2025)
Universal Design for Learning (UDL) is widely recognized as a framework to foster inclusive education, yet its successful adoption in elementary schools depends on multiple contextual and motivational factors. This study investigates how UDL is implemented and what drives teachers to adopt its principles. A systematic literature review (SLR) was conducted following PRISMA guidelines. Four databases (Scopus, ScienceDirect, Taylor Francis, and ProQuest) were searched using defined keywords and Boolean operators. Studies published between 2014 and 2024 that addressed UDL implementation in elementary schools were considered. After screening and applying inclusion and exclusion criteria, 12 empirical studies were selected. Self-Determination Theory (SDT) was used as the analytical lens to examine how autonomy, competence, and relatedness influence teachers’ motivation in adopting UDL. The synthesis identified key factors affecting UDL implementation, including teacher self-efficacy, knowledge of UDL principles, access to resources, professional development, and supportive school leadership. Teachers’ motivation, shaped by psychological needs, played a decisive role in sustaining UDL practices. Reported benefits of UDL included improved student engagement, equitable access to learning, reduced barriers for learners with disabilities, and enhanced instructional flexibility for teachers. This review highlights that both psychological motivation and institutional support are crucial for effective UDL implementation in elementary schools. Strengthening teacher training, fostering collaboration, and ensuring adequate resources are essential strategies to promote inclusive classrooms. The study provides theoretical and practical insights for educators and policymakers seeking to advance inclusive education through UDL.